Identificação de patógenos da cavidade bucal no lavado broncoalveolar de pacientes sob ventilação mecânica - Baptista, Ivany Machado de Carvalho [UNESP] (2014)
Critical patients admitted to intensive care unit (ICU), in their majority, require Invasive Mechanical Ventilation assistance (MV). The analysis of microbial diversity is fundamental to identifying species, as yet unknown, responsible for Pneumonia associated with mechanical ventilation (VAP). The objectives of this study were: to Study microbial diversity) present in the oral cavity and in the BAL (mini-BAL) of patients hospitalized in ICU under VM by Checkerboard DNA-DNA Hybridization technique; b) assess whether the microbial profile present in the oral cavity is present in Broncho Alveolar (mini-BAL), in different time periods of the MV (12 h, 48 ‘h, 96 h) and on extubation; c) detect the presence of bacterial species circulating in the bloodstream of patients hospitalized in ICU under VM through the results of blood cultures. Participated in this study 10 critical patients admitted to ICU under MV. The samples were collected on the dorsum of the tongue, subgingival space, in BAL, endotracheal aspirate and orotracheal intubation cannula. It was possible to identify the presence of bacterial species in the BAL/endotracheal aspirate, including with increased bacterial load with the extended time of orotraqueall Intubation (OTI), 48 h and 96 h; and in relation to the oral mucosa and subgingival space has also been possible to observe in the first 12 h the presence of bacterial species in the BAL, these findings showed association with VAP and with positive blood culture results. The isolated bacteria in blood culture were S auerus, S epidermides, P aeruginosa. There was association with fever and blood culture positive PAVM. It was concluded that during the OTI, bacterial species migrate quickly to the lower airways and may contribute to the pathophysiology of VAP. There were associations between VAP and Enterococcus faecalis, Fusobacterium periodonticum, Gemella morbillorum, Neisseria...